2023
DOI: 10.3390/ijerph20043395
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Online Search Activity and the Correlation with Daily New Cases of Monkeypox among 102 Countries or Territories

Abstract: Research assessing the trend in online search activity on monkeypox (mpox) and the correlation with the mpox epidemic at the global and national level is scarce. The trend of online search activity and the time-lag correlations between it and daily new mpox cases were estimated by using segmented interrupted time-series analysis and Spearman correlation coefficient (rs), respectively. We found that after the declaration of a Public Health Emergency of International Concern (PHEIC), the proportion of countries … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Additionally, even for physicians, only nearly one in three of them achieved a good level of knowledge [ 30 ]. Our previous studies found that the number of mpox cases was positively related with online search activity worldwide [ 31 , 32 ]. Therefore, China should promote health education on mpox-related knowledge and correct false information via multiple platforms, including Wechat, Weibo, or short-video platforms, when mpox cases are reported.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, even for physicians, only nearly one in three of them achieved a good level of knowledge [ 30 ]. Our previous studies found that the number of mpox cases was positively related with online search activity worldwide [ 31 , 32 ]. Therefore, China should promote health education on mpox-related knowledge and correct false information via multiple platforms, including Wechat, Weibo, or short-video platforms, when mpox cases are reported.…”
Section: Discussionmentioning
confidence: 99%